The Psychological Dynamics Underlying of Criminal Theft Accompanied by Violence - Agung Himawan; Suryanto; Niken Titi Pratitis (STKIP PGRI SIDOARJO, 2021)
This study was aimed to describe the forms of aggressive behavior by the perpetrator of the crime of theft which is accompanied by violence and the factors that cause the perpetrator to commit theft accompanied by violence. The method used in this research is a qualitative research method with a phenomenological approach by using observation and interview data collection techniques. The data analysis technique consists of the following stages: analyzing all data, categorizing data, compiling psychological dynamics, connecting with theoretical foundations, and drawing conclusions. Based on the results of the study, it is concluded that the forms of aggressive behavior committed by the perpetrators of criminal acts of theft accompanied by violence are verbal or symbolic aggression, namely in the form of harsh words, threatening, and cursing and physical aggressive behavior, namely: physical assault in the form of forcibly taking or confiscating the victim's property, hitting, injuring and injuring the victim using a sharp weapon.